Marketing Mix Strategy for Health Services Business: Bibliometric Analysis on Scopus Database - Rosidayani, Febby; Aini, Qurratul (Nusantara Science and Technology Proceedings, 2024)
Marketing is all the activities and processes that create, communicate, deliver, and offer value to clients, customers, colleagues, and the general public. Hospitals are semi-business healthcare organizations, which deal with marketing. Hospitals must use marketing to address problems and capitalize on opportunities, including the marketing mix. In finding the appropriate and most effective marketing plan to implement, any of the components of the marketing mix can be considered. Marketing has been considered the basis of strategic development in every industry around the world, regardless of whether the organization is engaged in products or services. This study aims to determine the development of marketing mix methods used by healthcare organizations from 2014 to 2023. The method used in this research is quantitative research with a literature study approach - analysis and visualization of literature using VOS viewer software. Data was collected by querying the Scopus database using relevant keywords, namely "healthcare" "marketing mix" AND "marketing management". The results showed an increase in publications on marketing mix over the past decade; in 2020, the highest number of research publications was found. The country that contributed the most to this theme was the United States and the authors who contributed the most were Eirod, J.K and Fortenberry, J.L. The discussion revealed that one of the aspects that companies can pay attention to in achieving the optimal and best marketing plan to implement is the marketing mix component. The conclusion of this study emphasizes the importance of the marketing mix as one of the most important factors for customers when making purchases. Suppose the company pays attention to what the customer is looking for. In this case, it is almost certain that the company will retain many opportunities to gain customers, and the goods offered will be well spent. The main limitation of this study is the use of data derived from the Scopus database.